Identifying Risk Factors Associated with Inappropriate Use of Acid Suppressive Therapy at a Community Hospital - Amandeep Singh; Vijay Bodukam; Kirit Saigal; Jaya Bahl; Yvette Wang; Alexandra Hanlon; Yinghui Lu; Michael Davis (Gastroenterology Research and Practice)
Purpose. By examining the prescribing patterns and inappropriate use of acid suppressive therapy (AST) during hospitalization and at discharge we sought to identify the risk factors associated with such practices. Methods. In this retrospective observational study, inpatient records were reviewed from January 2011 to December 2013. Treatment with AST was considered appropriate if the patient had a known specific indication or met criteria for stress ulcer prophylaxis. Results. In 2011, out of 58 patients who were on AST on admission, 32 were newly started on it and 23 (72%) were inappropriate cases. In 2012, out of 97 patients on AST, 61 were newly started on it and 51 (84%) were inappropriate cases. In 2013, 99 patients were on AST, of which 48 were newly started on it and 36 (75%) were inappropriate cases. 19% of the patients inappropriately started on AST were discharged on it in three years. Younger age, female sex, and 1 or more handoffs between services were significantly associated with increased risk of inappropriate AST. Conclusion. Our findings reflect inappropriate prescription of AST which leads to increase in costs of care and unnecessarily puts the patient at risk for potential adverse events. The results of this study emphasize the importance of examining the patient’s need for AST at each level of care especially when the identified risk factors are present.